ANALISA PENGARUH BOPO TERHADAP PROFITABILITAS PT. BPR SWADAYA ANAK NAGARI SIMPANG EMPAT - Roza Gustika (Jurnal Apresiasi Ekonomi, 2015)
Banking including BPR is very important to developing the economy. So, the bank must be have a level of optimal profitability continuously. This study to analized the effect of BOPO to Profitability of PT. BPR SAN. The data to be analized are the values of these variables in the quarterly report for the year 2010 - 2014. By the multiple linear regression analisys found that BOPO has a significant effect on NPM, but no significant effect on ROE and ROA. The implication of this research is PT. BPR SAN must improve the performance of credit porfolio in the ideal position and productive, but still have to consider the operational efficiency and the level of credit performance. Keywords: profitability, ROA, ROE and BOPO